World-Systems Analysis, Globalization, and Incorporated Comparison - Phillip McMichael (Journal of World-Systems Research, 2015)
When Immanuel Wallerstein (1974) subverted the mid-1970s social science scene with his concept of the world-system, development, the master concept of social theory, suffered a fatal blow. Wallersteins critique of development emphasized its misapplication as a national strategy in a hierarchical world where only some states can succeed. Wallersteins path-breaking epistemological challenge to the modernization paradigm reformulated the unit of analysis of development from the nation-state to the world-system. To be sure, the past three decades have seen reformulations, coined to address the failures of the development enterprise: frombasic needs, through participation in the world market, globalization, to local sustainability. But development, the organizing myth of our age, has never recovered.